Increased Expression of u-PA and u-PAR on Monocytes by LDL and Lp(a) Lipoproteins – Consequences for Plasmin Generation and Monocyte Adhesion - Ganné, Florence; Vasse, Marc; Beaudeu, Jean-Louis; Peynet, Jacqueline; François, Arnaud; Paysant, Jérôme; Lenormand, Bernard; Collet, Jean-Philippe; Vannier, Jean-Pierre; Soria, Jeannette; Soria, Claudine (Thrombosis and Haemostasis, 1999)
Monocyte-derived foam cells figure prominently in rupture-prone regions of atherosclerotic plaque. As urokinase/urokinase-receptor (u-PA/u-PAR) is the trigger of a proteolytic cascade responsible for ECM degradation, we have examined the effect of atherogenic lipoproteins on monocyte surface expression of u-PAR and u-PA. Peripheral blood monocytes, isolated from 10 healthy volunteers, were incubated with 10 to 200 µg/ml of native or oxidised (ox-) atherogenous lipoproteins for 18 h and cell surface expression of u-PA and u-PAR was analysed by flow cytometry. Both LDL and Lp(a) induced a dose-dependent increase in u-PA (1.6-fold increase with 200 μg/ml of ox-LDL) and u-PAR [1.7-fold increase with 200 μg/ml of ox-Lp(a)]. There is a great variability of the response among the donors, some of them remaining non-responders (absence of increase of u-PA or u-PAR) even at 200 μg/ml of lipoproteins. In positive responders, enhanced u-PA/u-PAR is associated with a significant increase of plasmin generation (1.9-fold increase with 200 μg/ml of ox-LDL), as determined by an amidolytic assay. Furthermore, monocyte adhesion to vitronectin and fibrinogen was significantly enhanced by the lipoproteins [respectively 2-fold and 1.7-fold increase with 200 μg/ml of ox-Lp(a)], due to the increase of u-PAR and ICAM-1, which are receptors for vitronectin and fibrinogen. These data suggest that atherogenous lipoproteins could contribute to the development of atheromatous plaque by increasing monocyte adhesion and trigger plaque weakening by inducing ECM degradation.